A Horizontally Transferred Plant Fatty Acid Desaturase Gene Steers Whitefly Reproduction. - Gong, C.; Guo, Z.; Hu, Y.; Yang, Z.; Xia, J.; Yang, X.; Xie, W.; Wang, S.; Wu, Q.; Ye, W.; Zhou, X.; Turlings, T.C.J.; et al. (Advanced science, 2024)
Polyunsaturated fatty acids (PUFAs) are essential nutrients for all living organisms. PUFA synthesis is mediated by ?12 desaturases in plants and microorganisms, whereas animals usually obtain PUFAs through their diet. The whitefly Bemisia tabaci is an extremely polyphagous agricultural pest that feeds on phloem sap of many plants that do not always provide them with sufficient PUFAs. Here, a plant-derived ?12 desaturase gene family BtFAD2 is characterized in B. tabaci and it shows that the BtFAD2-9 gene enables the pest to synthesize PUFAs, thereby significantly enhancing its fecundity. The role of BtFAD2-9 in reproduction is further confirmed by transferring the gene to Drosophila melanogaster, which also increases the fruit fly's reproduction. These findings reveal an extraordinary evolutionary scenario whereby a phytophagous insect acquired a family of plant genes that enables it to synthesize essential nutrients, thereby lessening its nutritional dependency and allowing it to feed and reproduce on many host plants.